AN ANALYSIS OF ATTITUDINAL LOYALTY IN SINGAPORE MEDICAL TOURISM FROM THE PERSPECTIVE OF INDONESIAN MEDICAL TOURISTS - Teresa, Cynthia; Adam, Mochammad Riyadh Rizky (APPS Publications, 2024)
The study examines the impact of destination familiarity, service quality, satisfaction, perceived value, trust, and destination image on the attitudinal loyalty of Mount Elizabeth Hospital (MEH) Singapore among Indonesian medical tourists. A quantitative study was conducted on 130 Indonesian medical tourists who live in Jakarta and have used medical services at Mount Elizabeth Hospital (MEH) Singapore within the last three months. To test the hypothesis, structural equation analysis is performed using PLS software. The findings suggest that there are positive associations between destination familiarity, destination image, and attitudinal loyalty to Mount Elizabeth Hospital (MEH) Singapore. Service quality has an indirect effect on attitudinal loyalty since satisfaction, perceived value, and trust operate as mediators. Finally, satisfaction, perceived value, and trust all have a favorable impact on Mount Elizabeth Hospital (MEH) Singapore's attitudinal loyalty.